Literasi Keuangan dan Dampaknya terhadap Perilaku Keuangan Generasi Z di Kabupaten Bandung Barat - Ageng Saepudin Kanda S; Dina Sephiani (STIKes Ibnu Sina Ajibarang, 2024)
A person’s level of knowledge, especially millennial generation (young people), regarding financial matters will definitely make life easier when making daily financial decisions. In the process, financial literacy can play major role. The aim of this research is to determine financial literacy and its impact on the financial behavior of generation Z in West Bandung Regency. The method used in this research is a descriptive quantitative method. The research results show that financial literacy has a significant impact on financial behavior in financial efficacy, investment knowledge, and debt management.A person’s level of knowledge, especially millennial generation (young people), regarding financial matters will definitely make life easier when making daily financial decisions. In the process, financial literacy can play major role. The aim of this research is to determine financial literacy and its impact on the financial behavior of generation Z in West Bandung Regency. The method used in this research is a descriptive quantitative method. The research results show that financial literacy has a significant impact on financial behavior in financial efficacy, investment knowledge, and debt management.